2015
DOI: 10.1007/s00455-015-9616-3
|View full text |Cite
|
Sign up to set email alerts
|

Penetration–Aspiration: Is Their Detection in FEES® Reliable Without Video Recording?

Abstract: Penetration-aspiration is known as the main finding in deglutition-disordered patients with implications for diagnostics and therapeutic management. Reliable detection of penetration-aspiration is given with fiberoptic endoscopic evaluation of swallowing (FEES(®)) as one of the gold standards in instrumental swallowing evaluation. The advice to implement video recording in FEES(®) to assure quality in identifying penetration-aspiration is often ignored, especially in bed-side settings. Thus, the aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
0
23
0
3
Order By: Relevance
“…Therefore, the reliability of the OPHL-PAS seems to be comparable to the reliability of the PAS in FEES. Slight differences of the reliability of the PAS among the studies may be the result of the influence of several factors, such as the clinical experience of the raters, the training, the number of views for each video and the retest interval [27,28,30]. Moreover, the different the statistical method used in the studies does not allow a direct comparison of the results as different concepts were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reliability of the OPHL-PAS seems to be comparable to the reliability of the PAS in FEES. Slight differences of the reliability of the PAS among the studies may be the result of the influence of several factors, such as the clinical experience of the raters, the training, the number of views for each video and the retest interval [27,28,30]. Moreover, the different the statistical method used in the studies does not allow a direct comparison of the results as different concepts were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Although VFSS is more widely available, we used FEES as our gold standard instrumental exam[18]. Prior studies have demonstrated excellent agreement between VFSS and FEES as well as good inter- and intra-rater reliability for both, however FEES is more sensitive for penetration and aspiration[4449]. VFSS requires transportation to fluoroscopy, which can be challenging in critically ill patients, whereas FEES can be performed at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities that are considered risk factors of dysphagia were also surveyed. The Penetration–Aspiration Scale (PAS), which is an eight‐point clinical scale for rating penetration and aspiration, was originally designed for videofluoroscopy; however, it was also used to compare the two groups because recent studies have reported the reliability of the PAS for FEES . The questionnaires, general conditions, functional impairment status, clinical assistance requirements, oral intake ability, and consciousness level were answered by a subject, a care person, and/or family caregiver in charge.…”
Section: Methodsmentioning
confidence: 99%